Handbook of research on next generation mobile communication systems - Panagopoulos, Athanasios D. (Advances in wireless technologies and telecommunication (AWTT), 2016)
This book offers solutions for optimal connection of mobile devices, from satellite signals to cloud technologies, by focusing on the ways communication is being revolutionized.